Battle for the Nether : an unofficial Minecrafter's adventure - Cheverton, Mark (Cheverton, Mark. Gameknight999 series, 2014)
The action-packed Minecraft follow-up to Invasion of the Overworld! Gameknight999, a real-life Minecraft user trapped inside the game he loves to play, and his friend Crafter have transported to a new server. Malacoda is the King of the Nether, a terrible ghast that wants to destroy all of Minecraft with his massive army of blazes, magma cubes, zombie pigmen, and wither skeletons. Knowing the lives of all those within Minecraft--as well as those in the physical world--are depending on them, Gameknight and Crafter will need to search the land to recruit an NPC army.